Dietary inclusion of IMTA-cultivated Gracilaria vermiculophylla in rainbow trout (Oncorhynchus mykiss) diets: effects on growth, intestinal morphology, tissue pigmentation, and immunological response - Araújo, Mariana (2020)
Dietary inclusion of IMTA-cultivated Gracilaria vermiculophylla was evaluated in rainbow trout. Growth and feed efficiency were determined in fish fed 0 % (CTRL), 5 % (G5), and 10 % (G10) of the red seaweed for 91 days. Carotenoid concentration (skin and muscle), immunological parameters, and intestinal morphology were also evaluated. G10 group showed the lowest final body weight, with feed and protein efficiency ratios being significantly lower than the CTRL. Although protein intake was similar among groups, G10 diet induced the lowest protein retention and gain probably due to its smallest intestine diameter and lowest villi height. Fish fed G10 diet displayed higher carotenoid content in the skin (16.7 μg g−1) when compared with the CTRL group, but a lower concentration was registered in the flesh (0.23 μg g−1). Instrumental color showed that fillets were more luminous (L*), less yellowish (b*), and more reddish (a*) with seaweed inclusion and the lowest chrome intensity (C*) in the G10 group confirmed the lowest muscle carotenoid content in these fish. G5 diet enhanced the innate immune response of rainbow trout inducing the highest peroxidase, alternative complement (ACH50), and lysozyme activities. The inclusion of Gracilaria meal in diets for rainbow trout is possible up to 5 %, but a higher inclusion level impairs growth.